From panegyric to defamation: the political language of Soviet propaganda in the 1920s and 1930s in periodicals - Dmitry Andreev; Maria Barabanova; Olga Belousova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article, based on materials from periodicals, examines discursive techniques of Soviet propaganda that were used by the authorities in the USSR in the interwar period to form a favorable ideological environment for themselves, strengthen the ideological attitudes of Soviet people, model their likes and dislikes, and hone collective negative sentiments common and characteristic of a significant segment of Soviet citizens towards individuals perceived by the system as hostile. The analysis of narratives from the periodical press is based on the methodological principles of G. Lasswell and N. Fairclough. Lasswell’s observation about the socializing significance of public emotions stimulated by the authorities and the resulting and articulated by this thinker “basic law of power”, according to which the process of ruling is reduced to making certain ideas perceived by the governed, are used in the analysis of speeches of party and state leaders, in systematizing the assessments expressed in the press, which honed the required perception of the political course pursued in the country. Fairclough’s concept of two locations of power – inside and outside the discourse – helps to clarify ideas about the propaganda techniques of the authorities in the period under study. For example, dialogism, thinking out loud, rhetorical questions found in public speeches were intuitively felt by representatives of power to maintain competitive advantages within the space of discourse, which, however, at the same time was guaranteed by the power monopoly of power both in the administrative vertical and in the public sphere, reflected and simultaneously formed by the media. A conclusion is made about an obvious tilt in the political language of power in the pre-war period towards increasing the emotional tension of society, maintaining it in an exalted state. For a situation of a stable and predictable agenda, the stake on the controlled and progressive “heating up” of public sentiment seemed justified. It made it possible to maintain a state of controlled conflict in relation to certain segments of the middle-level elite (“Prompartiya”) and to complete the construction of a homogeneous ideological space of the controlled. With the onset of war and the sharp increase in the uncertainty factor, the political language of the authorities should become more variable and flexible.